2011
DOI: 10.2340/00015555-1126
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Itch Characteristics Between Psoriasis and Atopic Dermatitis Patients: Results of a Web-based Questionnaire

Abstract: Differences in itch characteristics between different inflammatory dermatoses are not well described. The aim of this study was to assess differences in itch characteristics between patients with psoriasis and atopic dermatitis using a previously validated web-based questionnaire that was made available through the National Psoriasis Foundation and National Eczema Association for Science and Education websites. Participants rated frequency and intensity of itch, associated symptoms, itch descriptors, and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 8 publications
3
68
1
6
Order By: Relevance
“…It is well known that atopic hand dermatitis is very frequently accompanied by itch, but so far there are no studies that specifically address this issue. A web-based questionnaire study on itch characteristics showed that atopic dermatitis responders experienced itch more frequently and more intensely when compared to subjects suffering from psoriasis [24]. In patients with occupational CHE, those with irritant contact dermatitis reported significantly less intense itching than patients with irritant-induced atopic HE [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that atopic hand dermatitis is very frequently accompanied by itch, but so far there are no studies that specifically address this issue. A web-based questionnaire study on itch characteristics showed that atopic dermatitis responders experienced itch more frequently and more intensely when compared to subjects suffering from psoriasis [24]. In patients with occupational CHE, those with irritant contact dermatitis reported significantly less intense itching than patients with irritant-induced atopic HE [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that itching sensations may be experienced differently by each patient and depending on the underlying disease. O'Neill et al (6) and Reich et al (7) have shown that itching sensations can vary between various skin diseases.…”
mentioning
confidence: 99%
“…Itch · Mediators · Psoriasis · Pruritus · Stigmatization so die Pruritusstärke [17]. Während bei AE Patienten mehr Körperareale betrof fen waren, war bei Psoriatikern häufiger der Genitalbereich betroffen, und Scham gefühle im Zusammenhang mit dem Pru ritus wurden häufiger berichtet [17].…”
Section: Introductionunclassified
“…Während bei AE Patienten mehr Körperareale betrof fen waren, war bei Psoriatikern häufiger der Genitalbereich betroffen, und Scham gefühle im Zusammenhang mit dem Pru ritus wurden häufiger berichtet [17]. Von 100 Psoriasispatienten einer pol nischen Studie hatten 80% Pruritus, wo bei diese durch eine signifikant höhe re Krankheitsaktivität im PASI (Psoria sis Area and Severity Index) verglichen mit Psoriasispatienten ohne Pruritus auf fielen [23].…”
Section: Introductionunclassified